Improved cycleability of LiMn(2)O(4)-based thin films by Sn substitution - Shin, Dong Wook; Choi, Ji-Won; Choi, Won-Kook; Cho, Yong Soo; Yoon, Seok-Jin (AMER INST PHYSICS, 2008)
The spinel thin films of LiSn(x/2)Mn(2-x)O(4) prepared by pulsed laser deposition were studied in regards with electrochemical reversibility and discharge capacity. LiSn(0.0125)Mn(1.975)O(4) thin films possessed a large capacity of similar to 120 mA h g(-1) and a high capacity retention of > 81% relative to their initial capacity at 4 C after the 90th cycle. Such promising results are believed to originate from the Mn(4+)-richer spinel structure and the less distortion of MnO(6) octahedra. The near-edge x-ray-absorption fine structure result of the cycled LiSn(0.0125)Mn(1.975)O(4) films can be highlighted with the specific local t(2g) symmetry resulting from the interaction between Mn 3d and O 2p. (C) 2008 American Institute of Physics.
Keywords: LI-ION BATTERIES; DOPED SPINEL LIMN2O4; LITHIUM BATTERIES; CATHODE MATERIALS; CELLS; TRANSITION; LIXMN2O4; BEHAVIOR